To B (Bone Morphogenic Protein-2) or Not to B (Bone Morphogenic Protein-2): Mesenchymal Stem Cells May Explain the Protein’s Role in Osteosarcomagenesis - Xu, Chunfeng; Wang, Mingjie; Zandieh-Doulabi, Behrouz; Sun, Wei; Wei, Lingfei; Liu, Yuelian (Frontiers in Cell and Developmental Biology, 2021)
Osteosarcoma (OS), a primary malignant bone tumor, stems from bone marrow-derived mesenchymal stem cells (BMSCs) and/or committed osteoblast precursors. Distant metastases, in particular pulmonary and skeletal metastases, are common in patients with OS. Moreover, extensive resection of the primary tumor and bone metastases usually leads to bone defects in these patients. Bone morphogenic protein-2 (BMP-2) has been widely applied in bone regeneration with the rationale that BMP-2 promotes osteoblastic differentiation of BMSCs. Thus, BMP-2 might be useful after OS resection to repair bone defects. However, the potential tumorigenicity of BMP-2 remains a concern that has impeded the administration of BMP-2 in patients with OS and in populations susceptible to OS with severe bone deficiency (e.g., in patients with genetic mutation diseases and aberrant activities of bone metabolism). In fact, some studies have drawn the opposite conclusion about the effect of BMP-2 on OS progression. Given the roles of BMSCs in the origination of OS and osteogenesis, we hypothesized that the responses of BMSCs to BMP-2 in the tumor milieu may be responsible for OS development. This review focuses on the relationship among BMSCs, BMP-2, and OS cells; a better understanding of this relationship may elucidate the accurate mechanisms of actions of BMP-2 in osteosarcomagenesis and thereby pave the way for clinically safer and broader administration of BMP-2 in the future. For example, a low dosage of and a slow-release delivery strategy for BMP-2 are potential topics for exploration to treat OS.